Influence Of The Global Economic Policy Uncertainty Index On Inflation And Its Implications For Farmer Exchange Rates In Sulawesi Regions - Dewi Nur Asih; Nelson Metubun; Mohammad Zubair Hipy (Cita konsultindo, 2026)
The farmer exchange rate (FER) serves as a crucial parameter for assessing the extent to which the agricultural sector can support the livelihoods of farmers and contribute to local economic resilience. Considering the vital role of the agricultural sector in the regional economy, it is important to identify and analyze the factors influencing the fluctuations in the farmer exchange rate in order to formulate policies that can improve farmers' welfare and support more stable and sustainable agricultural sector development. The aim of this study is to analyze the relationship between global economic policy uncertainty, inflation, and the farmer exchange rate in the provinces of Sulawesi. This research adopts a quantitative approach, utilizing secondary data that includes the Global Economic Policy Uncertainty (GEPU) Index, inflation, and the farmer exchange rate in Sulawesi during the period from January 2024 to September 2025. The data used in this study consists of panel data comprising 126 observations (21 time-series data and 6 cross-sectional data), which are analyzed using panel data path analysis. The results of this study show that GEPU has a positive and significant effect on inflation, as well as a positive and significant effect on the farmer exchange rate in Sulawesi. However, the impact of GEPU on the farmer exchange rate becomes insignificant after being mediated by inflation. Inflation has been shown to have a negative impact on the farmer exchange rate, although its effect is not significant. Based on these findings, it is recommended that the government enhance the economic resilience of farmers through agricultural product diversification, strengthen inflation control policies, and improve extension services related to global uncertainties. Furthermore, collaboration between the government and the private sector in supporting the agricultural sector needs to be reinforced to create a more resilient and adaptive ecosystem in response to global changes.